Do left-wing governments decrease wage inequality among civil servants? - Kauder, Björn,Krause, Manuela,Potrafke, Niklas (CESifo, Center for Economic Studies & Ifo Institute, 2020)
We investigate whether left-wing governments decrease wage inequality among civil servants. The data is based on salaries of civil servants in the German states. Since a reform in 2006, German state governments are allowed to design salaries of civil servants. We employ encompassing data for pay levels and professions including judges, professors, policemen, and administrators and distinguish between levels of operating experiences. We use six wage inequality measures comparing salaries across pay levels and operating experiences. The results do not suggest that left-wing governments were more active in decreasing wage inequality among civil servants than center or right-wing governments. Cabinet members are civil servants themselves and decide on their own salaries: government ideology is also not shown to predict salaries of cabinet members. Because left-wing governments are perceived as taking action against income and wage inequality, future research should employ data from other federal states such as the United States to examine how government ideology influences salaries of civil servants.
10419/229541
Keywords: Graue Literatur; wage inequality; civil servants; government ideology; partisan politics; German states